The Effect of Job Loss and Unemployment Insurance on Crime in Brazil - Diogo Britto; Paolo Pinotti; Breno Sampaio (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2021)
We investigate the effect of job loss and unemployment benefits on crime, exploiting unique individual-level data on the universe of workers and criminal cases in Brazil over the 2009-2017 period. We find that the probability of criminal prosecution increases on average by 23% for workers displaced upon mass layoffs, and by slightly less for their cohabiting sons. Using causal forests, we show that the effect is driven entirely by young and low tenure workers, while there is no heterogeneity by education and income. Regression discontinuity estimates indicate that unemployment benefit eligibility completely offsets potential crime increases upon job loss, but this effect completely vanishes immediately after benefit expiration. Our findings point at liquidity constraints and psychological stress as main drivers of criminal behavior upon job loss, while substitution between time on the job and leisure does not seem to play an important role.
Keywords: K42; J63; J65; 330; unemployment; crime; unemployment insurance; registry data